(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article talks about the details of Pirimkul Kadirov’s trip to India, specifically, from Kashmir in the North to Bombay, Calcutta, and Madras regions in the south, in order to write historical novels about Babur Mirza and his descendants. In this travel diary, the information given in such sections as "Climate and Life", "Economy and Technology", "Responsibility of Ownership", "Human Will and State Control", "History", "Religion and Ethics" and Babur in each of them Interpretations and relationships related to Mirza and Baburi were discussed.